Inventering och klassificering av kvarlämnad virkesvolym vid slutavverkning - Stangebye, Jan (2007)
This final thesis is performed on commission of Hargs Bruk Ltd. Hargs Bruk manages one of Sweden's largest privately owned forests. A main part of the managed forest is situated in Roslagen in eastern Uppland. Since 1934 felling calculations have been performed within the estate every tenth year. According to the felling calculation from 2001 the share of standing volume broad-leaved trees should be at an average level of 18 %. Also according to this calculation the percentage by volume of broad-leaved trees in the thinning stands should be at a level of 21.4 % and in the final cut stands the percent by volume should be 14.6 %. These volumes are supposed to be brought in from an area of 18 322 hectares including small areas of waste land and stands with environmental restrictions at final cut operations. The reduction of the productive area is in total 1 354 hectares, about 7.4 %. From the total percent by volume of 14.6 % broad-leaved trees the company expects that, in these reduced areas, a level of 2.5 percentage units broad-leaved trees are situated. The expected result of the share of hardwood delivered is for that reason about 12 percent by volume. During the latest four years, the result of broad-leaved trees at final cut operations has been at a level of slightly 10% by volume. According to the calculations in this study the amount of hardwood that has been cut and delivered is 6 301 m3sk, in other words 8.8% by volume, during the years 2003 and 2004. According to this, the company wishes to investigate if the expected share of broad-leaved trees is left behind after final cut operations or if the final cut stands before final cut operations did not contain a share of broad-leaved trees to the extent that calculations show.